Towards Multilingual Biographical Event Extraction - Geierhos, Michaela; Bouraoui, Jean-Leon; Watrin, Patrick (Multilingual Resources, Multilingual Applications. Proceedings of the Conference of the German Society for Computational Linguistics and Language Technology (GSCL) 2011)
Within this paper, we describe the special requirements of a semantic annotation scheme used for biographical event extraction in the framework of the Europeancollaborative research project Biographe. This annotationscheme supports interlingual search for people due to its multilingual support covering four languages such as English, German, French and Dutch.
Keywords: Biographical Event Extraction for Interlingual People Search; Semantic Annotation Scheme